"Is It Not Possible to Be a Radical and a Christian?": Dorothy Day's Evolving Relationship with the Patriarchal Norms of Journalism and Catholicism. Issue 4 (27th December 2019) - Dick, Bailey
ABSTRACT: Journalist and Catholic activist Dorothy Day demonstrated her values through both actions with radical groups outside the conventional structures and norms for women of her time at the beginning of her career, and later through the small, quiet, daily acts of radicalism. As this article shows, through her leveraging and adherence to traditions and teachings, Day was able to access male-dominated spaces, gain legitimacy within the patriarchal structures, and later share her more radical, yet faithful, beliefs with readers and the Church to create change from within both the Church and the newspaper industry. Through an analysis of Day's personal papers, news articles, and memoirs, this article examines the way Day's experience as a journalist shaped her writing, activism, personal interactions, and understanding of the world.